Electromagnetic wave scattering on a dielectric cylinder in Born approximation - Syshchenko, V.V. (Вопросы атомной науки и техники, 2015)
The scattering of the plane electromagnetic wave on a spatially extended, fiber-lake target is considered. The fomula for the scattering cross section is obtained using the approximation analogous to Born one in quantum mechanics. Розглянуто розсіяння плоскої електромагнітної хвилі на просторово протяжної ниткуватої мішені. Отримано вираз для перерізу розсіяння з використанням наближення, що аналогічно борнівському наближенню у квантовій механіці. Рассмотрено рассеяние плоской электромагнитной волны на пространственно протяженной нитевидной мишени. Получено выражение для сечения рассеяния с использованием приближения, аналогичного борновскому приближению в квантовой механике.